The Current State of the Modernist Garden on Rua Santa Cruz: Contributions to the Conservation of Brazilian Landscape Heritage - Carmona-Ribeiro, Ana Carolina; Morais, Guilherme Fernandes de (Technical and Scientific Journal Green Cities, 2025)
Objective – To discuss the current state of the open spaces at the Casa Modernista on Santa Cruz street, currently known as Parque Modernista, based on extensive surveys carried out throughout 2023 and 2024 – aiming to disseminate the results of a work that can contribute to the recognition and valorization of Brazilian modernist landscape heritage, in light of the scenario of significant damage in these gardens.Methodology – Bibliographic review of Mina Klabin’s landscape design and further study of the gardens at Casa Modernista of Santa Cruz Street; analysis of primary sources related to the changes that the house and gardens have undergone, their use by Klabin-Warchavchik family and the site’s heritage listing; and systematic field surveys of the Parque today, collecting and systematizing data from different sources.Originality/Relevance – Considering that many Brazilian modernist gardens suffer from deterioration and loss of original characteristics, due to the lack of conservation policies, real estate market pressures, and other factors, the in-depth study of the history and material remainings of the Santa Cruz street gardens is extremely important, aiming to disseminate knowledge about their historical and artistic significance and to encourage their conservation as monuments and testimonies of a time of change and cultural effervescence in São Paulo.Results – Systematization of the main events that affected the modernist complex from its construction to its inauguration as Parque Modernista and Casa Modernista, in 2008. Observation and documentation of the site’s current use, along with the creation of architectural and landscape surveys that can support future interventions in the complex.Theoretical/Methodological Contributions – Tensioning of questionings about the modernist heritage in Brazil, haighlighting issues about its recognition and conservation, once these are spaces of memory, identity and symbolic production, broadening the debate on their conservation in a contemporary context.Social and Environmental Contributions – Expansion of the debate on Brazilian landscape heritage, by raising public awareness about its historical relevance and the need of conservation. Acknowledge of Mina Klabin as a pioneering figure in nacional landscape field, highlighting the lack of academic studies dedicated to her role in Brazilian modernist context. Strengthening of efforts to conservate the Parque Modernista, recognizing it as part of urban environmental heritage of São Paulo. Enrichment of knowledge about vegetation, topography, furnishings and equipments, under technical and environmental analysis, contributing to future actions of valorization and qualified management of the complex.
Keywords: Landscape heritage; Mina Klabin Warchavchik; Modern landscaping